Association Between Mortality and Heritability of the Scale of Aging Vigor in Epidemiology. Issue 8 (13th June 2016) - Sanders, Jason L.; Singh, Jatinder; Minster, Ryan L.; Walston, Jeremy D.; Matteini, Amy M.; Christensen, Kaare; Mayeux, Richard; Borecki, Ingrid B.; Perls, Thomas; Newman, Anne B.; ,
Abstract : Objectives: To investigate the association between mortality and heritability of a rescaled Fried frailty index, the Scale of Aging Vigor in Epidemiology (SAVE), to determine its value for genetic analyses. Design: Longitudinal, community‐based cohort study. Setting: The Long Life Family Study (LLFS) in the United States and Denmark. Participants: Long‐lived individuals (N = 4, 875, including 4, 075 genetically related individuals) and their families (N = 551). Measurements: The SAVE was administered to 3, 599 participants and included weight change, weakness (grip strength), fatigue (questionnaire), physical activity (days walked in prior 2 weeks), and slowness (gait speed); each component was scored 0, 1, or 2 using approximate tertiles, and summed (range 0 (vigorous) to 10 (frail)). Heritability was determined using a variance component–based family analysis using a polygenic model. Association with mortality in the proband generation (N = 1, 421) was calculated using Cox proportional hazards mixed‐effect models. Results: Heritability of the SAVE was 0.23 ( P < .001) overall (n = 3, 599), 0.31 ( P < .001) in probands (n = 1, 479), and 0.26 ( P < .001) in offspring (n = 2, 120). In adjusted models, higher SAVE scores were associated with higher mortality (score 5–6: hazard ratio (HR) = 2.83, 95% confidence interval (CI) = 1.46–5.51; score 7–10: HR = 3.40, 95% CI = 1.72–6.71) than lower scores (0–2). Conclusion: The SAVE was associated with mortality and was moderately heritable in the LLFS, suggesting a genetic component to age‐related vigor and frailty and supporting its use for further genetic analyses.